Labour Productivity in ASEAN Countries in the Case of COVID-19 Pandemic - Yeap, Joyce Ke Xin; Lim, Zi Suen; Pung, Wei Hong; Yap, Chun Yong (2022)
To identify the factors that affect the labour productivity in ASEAN countries during COVID-19 pandemic. To determine the effect of government efficiency on labour productivity in ASEAN countries during COVID-19 pandemic. To examine the effects of gross fixed capital formation, employment on labour productivity in ASEAN countries during COVID-19 pandemic.